PELATIHAN EKONOMI KREATIF DALAM MEMANFAATKAN POTENSI DESA UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA BANDAR KEC. SOSOH BUAY RAYAP KAB. OKU (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Creative economy actors in Bandar village are still low and there is a lot of potential that has not been maximized. If you look at the potentials that exist in Bandar village, the agricultural sector is one sector that supports the economy in the area but has not been optimized properly whether there are other economic opportunities. The purpose of this Community Service (PPM) activity is to identify what village potentials can be creative economic opportunities in Bandra Village and what factors are obstacles to creative economic opportunities in Bandar Village. The results of the research or discussion stated that the potential in Bandar village is related to agricultural and plantation products where the community mostly cultivates land to grow rice in rice fields and fields, besides corn, rubber, citrus fruits, and rubber, the potential for the creative economy is woven bamboo and nature tourism. Lack of knowledge related to low human resources, lack of awareness of utilizing village potential, people accustomed to doing everything but not being focused, lack of village role in fostering bamboo weavers, lack of capital is an inhibiting factor.